Pengaruh Store Atmosphere, Product Assortment dan Harga Terhadap Minat Beli Pada Lottemart Center Point Medan - Demak Claudia Yosephine Simanjuntak; Edward Nasareth Samosir; Teresia Indah Sari Simamora (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Lotte Mart Center Point Medan is a company engaged in trading services with a wholesale sales system. Lottemart Center Point Medan strives to continue to increase consumer buying interest. The purpose of research is to find out partially and simultaneously the influence of store atmosphere, product variety, and the price of consumer buying interest at Lotte Mart Center Point Medan. The research method used is descriptive quantitative. The independent variables of this research are store atmosphere, product variety, and price. The dependent variable of the study is buying interest. The population technique in this study uses an unlimited population because the population in this study is not possible to be calculated as a whole, so the population is all consumers who visit Lotte Mart Center Point Medan. The sampling method in this study was purposive sampling with a total of 90 people. Data collection techniques were carried out by observation, interviews, and questionnaires. The data were then analyzed using the F test and t test. The results of the study found that store atmosphere, product variety, and prices at Lotte Mart Center Point Medan had an effect on buying interest simultaneously and partially. The magnitude of the influence of store atmosphere, product variety, and price on buying interest at Lotte Mart Center Point Medan is 88.4%, while 11.6% is influenced by variables other than careful variables.